The key to my heart : a novel - Louis, Lia (Emily Bestler Books/Atria, 2022)
Sparkly and charming Natalie Fincher has it all, a handsome new husband, a fixer-upper cottage of her dreams, and the opportunity to tour with the musical she's spent years writing. But when her husband suddenly dies, all her hopes and dreams instantly disappear. But when someone begins to mysteriously leave the sheet music for her husband's favorite songs at the train station's public piano, Natalie begins to feel a sense of hope and excitement for the first time. As she investigates just who could be doing this, Natalie finds herself on an unexpected journey toward newfound love for herself, for life, and maybe, for a special someone.